Profissionais da saúde 50+: a utilização de tecnologias e as vivências de perdas e lutos durante a pandemia da covid-19 - Areco, Felipe de Souza (Universidade Federal de São Carlos, 2025)
The Covid-19 pandemic presented numerous challenges to healthcare professionals, who faced the dual pressures of rapidly adapting to modern technologies and managing the emotional toll of the sudden loss of patients. This study aims to understand the experiences of healthcare professionals, focusing on the use of technologies and the process of grief during the fight against Covid-19. The main objective of this work was to comprehend the experiences of healthcare professionals aged 50 and over who were on the pandemic's frontlines, emphasizing the use of technologies and the emotional impact of patient loss. Additionally, the research sought to explore how these professionals coped with grief and how team-based experience-sharing and reflections on death supported their emotional resilience. The study employed a qualitative approach, conducting interviews with healthcare professionals over 50 years old who were directly involved in the Covid-19 response. The interviews addressed topics related to the use of technologies for communication with patients and their families, as well as the emotional experiences surrounding grief from the loss of patients. The sample included professionals from various healthcare fields, such as physicians, nurses, and other members of intensive care teams. The theoretical framework adopted for analyzing the experiences of healthcare professionals was phenomenology. By applying this approach, the research sought to understand how healthcare professionals emotionally experienced the pandemic, encompassing the technological challenges and the impact of grief, while preserving the individuality and subjectivity of each experience. The results revealed that adapting to modern technologies was a significant challenge, particularly regarding remote communication with patients and their families. Many professionals reported initial difficulties using digital platforms but also acknowledged the importance of these tools in maintaining connections with patients and providing emotional support to their families. Furthermore, the sudden loss of patients due to Covid-19 deeply affected the emotional well-being of professionals, many of whom expressed feelings of helplessness, frustration, and anticipatory grief. The exchange of experiences among team members and the opportunity to reflect on grief were highlighted as key resources for supporting the emotional coping of these professionals. The study concludes that healthcare professionals aged 50 and over faced significant challenges during the pandemic, both technological and emotional. While the use of technologies was critical for continuing care, it required rapid adaptation and training strategies. The emotional impact of patient loss, especially in the context of sudden deaths caused by Covid-19, necessitated continuous psychological support and collective reflection practices, such as team experience-sharing. The research emphasizes the importance of providing ongoing emotional support and adequate training to healthcare professionals to ensure their mental health and well-being in the face of the pandemic’s challenges.
Healthcare professionals 50+: the use of technologies and the experiences of loss and grief during the covid-19 pandemic
Keywords: Pandemia; Profissionais de saúde; Tecnologia; Luto; Fenomenologia; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA